Psychoanalysis of the Character's Anxiety Emotion in Script Inside Out 2 Movie - Taufan, Azhar Shakti; Tawami, Tatan (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2024)
This research is titled "Psychoanalysis of the Character's Anxiety Emotion in Script Inside Out 2," which aims to analyze the personality structure of the emotion character Anxiety in Riley's life. Sigmund Freud's psychoanalytic theory is used to identify the personality structure by analyzing the id, ego, and superego. Through the qualitative descriptive method, the personality structure of the character Anxiety in the film ‘Inside Out 2’ was successfully identified. The research findings show that the character Anxiety is dominated by a balance between the ego and superego. Anxiety is identified not only as a mediator between the id and superego but also as an element that ensures Riley adheres to the established moral standards. The character Anxiety in this film represents the constant tension between instinctual drives, moral demands, and the reality that must be faced, which significantly influences its behavior and responses to the situations Riley encounters. Keywords: Inside Out 2, Anxiety, Psychoanalysis, Sigmund Freus, Personality Structure